On the Radio Polarization Signature of Efficient and Inefficient Particle Acceleration in Supernova Remnant SN 1006 - Reynoso, Estela Marta (2013)
Radio polarization observations provide essential information on the degree of order and orientation of magnetic fields, which themselves play a key role in the particle acceleration processes that take place in supernova remnants (SNRs). Here we present a radio polarization study of SN 1006, based on combined Very Large Array and Australia Telescope Compact Array observations at 20 cm that resulted in sensitive images with an angular resolution of 10 arcsec. The fractional polarization in the two bright radio and X-ray lobes of the SNR is measured to be 0.17, while in the southeastern sector, where the radio and non-thermal X-ray emission are much weaker, the polarization fraction reaches a value of 0.6 ± 0.2, close to the theoretical limit of 0.7. We interpret this result as evidence of a disordered, turbulent magnetic field in the lobes, where particle acceleration is believed to be efficient, and a highly ordered field in the southeast, where the acceleration efficiency has been shown to be very low. Utilizing the frequency coverage of our observations, an average rotation measure of ~12 rad m-2 is determined from the combined data set, which is then used to obtain the intrinsic direction of the magnetic field vectors. While the orientation of magnetic field vectors across the SNR shell appear to be radial, a large fraction of the magnetic vectors lie parallel to the Galactic plane. Along the highly polarized southeastern rim, the field is aligned tangent to the shock, and therefore also nearly parallel to the Galactic plane. These results strongly suggest that the ambient field surrounding SN 1006 is aligned with this direction (i.e., from northeast to southwest) and that the bright lobes are due to a polar cap geometry. Our study establishes that the most efficient particle acceleration and generation of magnetic turbulence in SN 1006 is attained for shocks in which the magnetic field direction and shock normal are quasi-parallel, while inefficient acceleration and little to no generation of magnetic turbulence are obtained for the quasi-perpendicular case.